2009
DOI: 10.1002/adfm.200801212
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of PbS Nanocrystals by Bovine Serum Albumin in its Native and Denatured States

Abstract: PbS nanocrystals (NCs) are synthesized in aqueous phase within a temperature range of 40–80 °C in the presence of native and denatured states of bovine serum albumen (BSA) as the capping/stabilizing agent. The NCs are characterized with the help of field‐emission scanning electron microscopy, high‐resolution transmission electron microscopy, X‐ray diffraction, and energy‐dispersive X‐ray analysis. At 40 °C, large ball‐shaped NCs (145 ± 37 nm) with small surface protrusions are formed when 1 × 10−4 g mL−1 BSA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…BSA, a ubiquitous plasma protein with a molecular weight of 66,500 Da, is composed of 580 amino acid residues [23,24]. Due to their wide hydrophobic, hydrophilic, anionic, and cationic properties, BSA has been extensively used as a model protein in many fields including drug delivery [25], biomimetic mineralization [26], nanomaterial synthesis [27,28], surface modification and intermolecular interaction [29], etc.…”
Section: Resultsmentioning
confidence: 99%
“…BSA, a ubiquitous plasma protein with a molecular weight of 66,500 Da, is composed of 580 amino acid residues [23,24]. Due to their wide hydrophobic, hydrophilic, anionic, and cationic properties, BSA has been extensively used as a model protein in many fields including drug delivery [25], biomimetic mineralization [26], nanomaterial synthesis [27,28], surface modification and intermolecular interaction [29], etc.…”
Section: Resultsmentioning
confidence: 99%
“…The interactions between protein and nanoparticles do not poison the whole surface of the metallic entity, as we have shown in the concentration-dependent suppression of the biological activity of virus HIV-1 (Elechiguerra et al 2005). BSA protein has also been widely used as stabilizing agent for nanomaterials (Bakshi et al 2009;Bunker et al 2007;Meziani et al 2005;Shang et al 2007). Interestingly, shape-control of platinum nanoparticles using BSA as capping agent has not been reported.…”
Section: Introductionmentioning
confidence: 90%
“…BSA is a globular protein consisting of a single polypeptide chain with 583 amino acid residues, and its ability to form complexes with different noble-metal nanoparticles has been studied previously with silver (Elechiguerra et al 2005), gold (Burt et al 2004), platinum (Burt 2007), and others (Bakshi et al 2009). The interactions between protein and nanoparticles do not poison the whole surface of the metallic entity, as we have shown in the concentration-dependent suppression of the biological activity of virus HIV-1 (Elechiguerra et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As their absorption and emission wavelength depend on the dot size, which can easily be controlled during synthesis, they are extremely attractive as building blocks for nanophotonic applications. Nowadays, they have found a wide range of potential applications in biosensors, chemical sensors, photovoltaic cells, light amplifiers, and light emitting diodes [33,34]. Recently, it was also demonstrated that such materials have also a large nonlinear refractive index 2 at telecom wavelengths, which raises a large interest in their possible application as nonlinear optical materials for photonics (e.g., like for optical switching, holography gratings, and spectral filtering).…”
Section: Colloidal Quantum Dotsmentioning
confidence: 99%
“…For the near-infrared spectral range, lead-based colloidal QDs are of considerable interest due to their unique optical and electronic properties [33,34]. Their absorption and emission wavelengths depend on the dot size, which can be easily controlled during chemical synthesis.…”
Section: Iii/v Colloidal Quantum Dotsmentioning
confidence: 99%